Pengaruh Tingkat Pendidikan Dan Pengalaman Kerja Terhadap Produktivitas Kerja Karyawan Pada Kantor Balai Penelitian Dan Pengembangan Teknologi Pengelolaan Daerah Aliran Sungai Surakarta - Indriani Lestari P.D, Wahyu; , Drs. Ma'ruf, MM (2017)
This study aims to determine the level of education and work experiences have a positive and significant impact on employee work productivity partially and simultaneously. The method of this research was conducted at the Office of Research and Development of Surakarta River Watershed Technology, with the population of all employees and the sample used in this research is 100 employees at the Office of Research and Development of Surakarta River Surface Management Technology. The research technique uses causal research is to identify the causal relationship between the variables that serve as the cause and which variable serves as the result variable. Methods of collection using questionnaires. (2) Classic Test (Normality Test, Multicollinearity Test and Heteroskedasticity Test), (3) Hypothesis Testing (Multiple Linear Analysis, t test, F test and Coefficient Determination). The results of the data analysis can be obtained that: (1) the result of t test analysis shows the level of education and work experience have an effect on the work productivity of PT Misaja Mitra Pati partially and (2) the result of F test analysis show the level of education and work experience have an effect on the Work Productivity of PT Misaja Mitra Pati simultan.